Hero - Grant, Michael, 1954- (2019)
While the Rockborn Gang tries to outmaneuver a new supervillain created by meteorite shrapnel, Malik investigates the Dark Watchers and the possibility that their reality is advanced, elaborate simulation.
Keywords: Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Good and evil -- Juvenile fiction; Science fiction; Young adult fiction